2009
DOI: 10.1002/jts.20456
|View full text |Cite
|
Sign up to set email alerts
|

The effect of interpersonal psychotherapy for depression on insomnia symptoms in a cohort of women with sexual abuse histories

Abstract: Insomnia frequently occurs with trauma exposure and depression, but can ameliorate with improvements in depression. Insomnia was assessed by the insomnia subscale of the Hamilton Rating Scale for Depression in 106 women with childhood sexual abuse (CSA) and major depression receiving Interpersonal Psychotherapy in an uncontrolled pilot (n = 36) and an immediately subsequent randomized controlled trial (n = 70) comparing IPT to treatment as usual. Depression improved in each study and in both treatment conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
(21 reference statements)
2
16
0
Order By: Relevance
“…A randomized trial of interpersonal psychotherapy was conducted among women with major depression and a history of childhood sexual abuse [54]. The authors found that interpersonal psychotherapy resulted in significant improvements in depression severity (measured using multiple depression scales), but did not result in any significant improvements in insomnia severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A randomized trial of interpersonal psychotherapy was conducted among women with major depression and a history of childhood sexual abuse [54]. The authors found that interpersonal psychotherapy resulted in significant improvements in depression severity (measured using multiple depression scales), but did not result in any significant improvements in insomnia severity.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that interpersonal psychotherapy resulted in significant improvements in depression severity (measured using multiple depression scales), but did not result in any significant improvements in insomnia severity. Thus, it appears as though survivors of ACEs with insomnia may require more complex therapy than those without insomnia [54]. Additionally, there is evidence that patients with sleep disorders and a history of ACEs require different treatment than those without a history of ACEs.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of sleep problems in PTSD has also been shown to reduce PTSD symptoms in addition to improving sleep (Germain, 2013; Schoenfeld, Deviva, & Manber, 2012). However, the treatment of sleep disturbances in the context of these disorders may differ based on trauma history: A randomized clinical trial involving the use of interpersonal psychotherapy found that patients with current depression and a history of CSA showed less improvement in insomnia symptoms than those without CSA (Pigeon et al, 2009). Other studies corroborate the result that therapy may need to differ based on CSA history (Cort et al, 2012; Lewis et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…As both sleep and CSA have their own negative influences on both mental and physical health, a better understanding of sleep disturbances in adults with CSA histories, which involves elucidating the effect of incident characteristics on sleep and determining gender differences, is important. Treatment of trauma-exposed individuals is complex, and as such, the effectiveness of interventions on sleep (and other related outcomes such as psychopathology) may differ based on CSA status (Cort et al, 2012; Lewis et al, 2010; Pigeon et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…13 Although complete recovery is the goal of depression treatment, this is often an elusive goal, and sleep disturbances are among the most common residual symptoms. 46 A recent study found a residual insomnia rate of 51% among patients who showed remission of other depressive symptoms following 20 weeks of either cognitive behavioral therapy or pharmacotherapy. 7 …”
mentioning
confidence: 99%